Nickel and sulfur modified biomass derived carbon-based sulfide electrode material as well as preparation method and application thereof
Through the preparation method of biomass-derived carbon-based sulfide electrode materials modified by nickel and sulfur, the problem of insufficient catalytic activity and stability of existing carbon-based sulfide electrode materials is solved, and more efficient in the process of electrolyzing hydrogen production is achieved. , more stable catalytic effect.
Patent Information
- Application Number
- CN202411468402.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-02-14
AI Technical Summary
The existing carbon-based sulfide electrode materials have shortcomings such as limited catalytic intrinsic activity and poor stability in terms of catalysis, and it is difficult to meet the efficient and stable needs in the fields of electrolytic hydrogen production.
The biomass-derived carbon-based sulfide electrode material modified with nickel and sulfur, and the preparation method includes reacting the biomass material with compounds such as dopamine hydrochloride, cobalt nitrate hexahydrate and nickel hexahydrate at room temperature, and then with the sulfur source at Carbonization and vulcanization reaction are carried out at high temperature to form a composite structure of nickel-modified cobalt sulfide nanoparticles and sulfur-doped carbon nanotubes.
It significantly improves the catalytic activity and stability of the electrode material, can produce higher urea oxidation current density at lower electric potential, and shows good stability in the process of electrolyzing hydrogen production, broadening its in electrolyzing water production Application prospects in the hydrogen field.
Smart Images

Figure CN119433597A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrocatalytic materials, and in particular relates to a nickel-sulfur-modified biomass-derived carbon-based sulfide electrode material, and a preparation method and application thereof. Background Art
[0002] With the in-depth exploration and pursuit of renewable energy around the world, hydrogen energy, with its clean and efficient characteristics, has gradually emerged and become the new favorite in the energy field. As the core link in the hydrogen energy industry chain, the technological progress and application of electrolytic hydrogen production technology are crucial to promoting the vigorous development of the hydrogen energy economy. Electrolytic hydrogen production is essentially the process of converting hydrogen ions into hydrogen gas by electrolyzing water, and catalysts play a vital role in this process. For a long time, precious metal catalysts such as platinum and palladium have dominated the field of electrolytic hydrogen production due to their excellent catalytic activity and stability. However, the high cost, scarcity of resources and potential deactivation problems have greatly limited their application in large-scale production. In order to break through this bottleneck, researchers are actively exploring new, efficient and stable non-precious metal catalysts. These catalysts are not only low-cost and stable in performance, but also can work under a wider range of conditions, providing new possibilities for the popularization and application of electrolytic hydrogen production technology.
[0003] In the field of materials science, transition metal sulfides (TMDs) have attracted much attention for their unique electronic, optical and mechanical properties. As a member of non-precious metal catalysts, they show great application potential in fields such as energy conversion and storage. However, in practical applications, transition metal sulfides still have problems such as poor stability and insufficient conductivity. To solve these problems, researchers have proposed strategies to construct carbon-based sulfides. However, existing carbon-based sulfides have shortcomings in catalysis, such as limited intrinsic catalytic activity and poor stability.
[0004] Biomass-derived carbon materials, as a high-performance carbon material derived from renewable biomass resources, have the advantages of being environmentally friendly and resource-rich. Through specific pyrolysis or chemical conversion processes, these materials not only successfully retain the original porous structure and excellent conductive properties of biomass, but also further endow it with unique surface chemical properties. More importantly, its renewable raw material source and environmentally friendly production process make it show great application potential in energy storage, environmental governance, catalyst carriers and other fields, becoming one of the key materials for achieving green circular economy and sustainable development. Carbon-based sulfide electrode materials based on biomass carbon materials not only realize the high-value-added transformation and utilization of biomass resources, but also open up a new path for the research and development of high-performance electrode materials, thus opening up a promising research direction at the intersection of biomass resource circular economy and carbon-based sulfide material science. However, the application of biomass carbon materials in the preparation of carbon-based sulfides still faces a series of technical problems that need to be solved. This includes selecting biomass precursors with high carbon content and rich heteroatom structures, optimizing the preparation process to reduce energy consumption and shorten time costs, achieving effective introduction and tight bonding of sulfur elements to inhibit the dissolution and shuttle effect of polysulfides, accurately controlling the pore structure to meet diverse application needs, and improving the cycle stability of electrode materials. Only by overcoming these challenges can we promote the continuous progress of biomass carbon-based sulfide electrode materials and promote their widespread promotion in practical applications.
[0005] Therefore, it is very necessary to develop a biomass-derived carbon-based sulfide electrode material with excellent catalytic performance. Summary of the invention
[0006] The technical problem to be solved by the present invention is to overcome the deficiencies and defects mentioned in the above background technology and provide a nickel-sulfur-modified biomass-derived carbon-based sulfide electrode material and a preparation method and application thereof.
[0007] In order to solve the above technical problems, the technical solution proposed by the present invention is: A method for preparing a nickel-sulfur modified biomass-derived carbon-based sulfide electrode material comprises the following steps: (1) Dispersing the biomass material evenly in deionized water; (2) adding dopamine hydrochloride, tris(hydroxymethyl)aminomethane, cobalt nitrate hexahydrate and nickel nitrate hexahydrate to the solution obtained in step (1), stirring the mixture at room temperature to react, and after the reaction is completed, washing and drying to obtain a precursor of a nickel-sulfur modified biomass-derived carbon-based sulfide electrode material; (3) The precursor obtained in step (2) is subjected to a high-temperature carbonization and sulfurization reaction with a sulfur source under a protective atmosphere, and upon completion of the reaction, a nickel-sulfur modified biomass-derived carbon-based sulfide electrode material is obtained.
[0008] The present application uses dopamine hydrochloride, tris(hydroxymethyl)aminomethane, cobalt nitrate hexahydrate and nickel nitrate hexahydrate and biomass materials to prepare a precursor, synthesizes a polydopamine film during the reaction of dopamine hydrochloride, and adsorbs cobalt ions and nickel ions onto the surface of the biomass material; subsequently, a sulfur source is added for simultaneous high-temperature pyrolysis conversion, and the polydopamine film and the biomass material are pyrolyzed into carbon at a high temperature, wherein polydopamine is catalyzed and pyrolyzed under the joint action of transition metals and sulfur powder to form sulfur-doped carbon nanotubes attached to the surface of biomass carbon, and the adsorbed cobalt and nickel ions undergo a carbon thermal reduction reaction during the pyrolysis process to be converted into metal elements, and react with sulfur to generate nickel-modified cobalt sulfide nanoparticles, which are coated on the top of the carbon nanotubes.
[0009] Through the carefully designed synthesis steps of this application, sulfides can be stably and evenly loaded on the conductive substrate, significantly improving their catalytic activity and stability. This modification method not only combines the unique properties of transition metal sulfides, but also utilizes the excellent conductivity of the conductive substrate, providing a new idea for efficient and stable energy conversion.
[0010] Preferably, the biomass material in step (1) is poplar fiber or reed fiber, and the diameter of the poplar fiber or reed fiber is 10-14 um. As the source of biomass carbon, poplar fiber and reed fiber have the advantages of abundant raw materials, good fiber quality, environmental friendliness, strong sustainability, low cost and high added value. These advantages make poplar fiber and reed fiber have broad prospects in the preparation and application of biomass carbon.
[0011] Preferably, the volume ratio of the biomass carbon added to the deionized water in step (1) is 0.02-0.04:10, in g / mL; the dispersion is performed by ultrasound, and the ultrasound time is controlled to be 0.5-1h. Soaking the biomass material in deionized water for ultrasonic dispersion in advance is conducive to the uniform loading of other components on the biomass material in the subsequent reaction.
[0012] Preferably, in step (2), the concentration of dopamine hydrochloride is 0.020-0.022 mol / L, the concentration of tris(hydroxymethyl)aminomethane is 0.015-0.017 mol / L, the concentration of cobalt nitrate hexahydrate and nickel nitrate hexahydrate is 0.005-0.007 mol / L, and the reaction time is 22-26h. Low nickel and cobalt concentrations or short soaking time may result in too little adsorption of nickel and cobalt ions, which is not conducive to the adsorption of nickel and cobalt ions on the surface of biomass materials; high nickel and cobalt ion concentrations and long soaking time will result in excessive adsorption of nickel and cobalt ions, which is not conducive to the growth of subsequent active components and is prone to agglomeration.
[0013] More preferably, the concentration of dopamine hydrochloride is 0.021 mol / L, the concentration of tris(hydroxymethyl)aminomethane is 0.016 mol / L; the concentration of cobalt nitrate hexahydrate and nickel nitrate hexahydrate are both 0.06 mol / L, which can achieve the best effect.
[0014] Preferably, the protective atmosphere in step (3) is nitrogen, and the mass ratio of the precursor of the nickel-sulfur modified biomass-derived carbon-based sulfide electrode material to the sulfur content in the sulfur source is 0.8-1.2:0.8-1.2; the specific temperature of the high-temperature carbonization and sulfurization reaction is: firstly heating to 400-600°C at a heating rate of 2-10°C / min, and keeping warm for 1-4h; then heating to 890-910°C at a heating rate of 2-10°C / min, and keeping warm for 1-4h.
[0015] For the nickel and sulfur modified biomass derived carbon-based sulfide electrode material precursor in the present invention, the present invention adopts a synchronous high-temperature carbonization and sulfurization treatment method with stage heating and stage insulation, which is beneficial to the modification of the material and reduces the influence on the transition metal loaded on the material, which is beneficial to improve the catalytic activity and stability of the electrode material.
[0016] Preferably, the precursor and the sulfur source are located at two ends of the reaction container respectively during the high-temperature carbonization and sulfurization reaction to perform synchronous reaction.
[0017] Under the same technical concept, the present application also provides a nickel-sulfur modified biomass-derived carbon-based sulfide electrode material, and the electrode material is prepared by the preparation method.
[0018] Preferably, the nickel-sulfur modified biomass carbon-based sulfide electrode material uses biomass material as a matrix, sulfur-doped carbon nanotubes are uniformly loaded on the matrix, and the top of the carbon nanotubes is coated with nickel-modified cobalt sulfide particles.
[0019] Preferably, the carbon nanotubes have a diameter of 20-80 nm and a length of 1-5 μm, and the chemical formula of the electrode material is (Co, Ni)9S8@SNC / SCWF.
[0020] Under the same technical concept, the present application also provides an application of a nickel-sulfur-modified biomass-derived carbon-based sulfide electrode material, wherein the nickel-sulfur-modified biomass-derived carbon-based sulfide electrode material is used for urea-assisted water electrolysis to produce hydrogen.
[0021] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention provides a nickel-sulfur modified biomass-derived carbon-based sulfide electrode material. This material is based on nickel and sulfur modification. Through a specific modification process, the electronic structure of the active site is synergistically regulated. At the same time, the modification of anions and cations enhances the interaction between biomass carbon and heterogeneous active components. In the present invention, PDA provides the carbon source required for the growth of carbon nanotubes, and sulfur powder provides the sulfur source. The degree of defects in carbon materials is increased by sulfur-doping carbon nanotubes, which is conducive to further enhancing the interfacial interaction and optimizing the electronic structure of the electrocatalytic active site; (2) When the nickel-sulfur modified biomass-derived carbon-based sulfide electrode material provided by the present invention is applied to urea-assisted water electrolysis to produce hydrogen, it can produce a higher urea oxidation current density at a lower potential and better stability, thereby greatly broadening its application prospects in the field of water electrolysis to produce hydrogen; (3) The preparation method of the present invention makes full use of the characteristics of biomass materials such as renewability, low cost and environmental friendliness, which not only reduces the preparation cost of electrode materials, but also expands the high value-added application of biomass. In addition, the high specific surface area and chemical activity of biomass itself enable the prepared electrode materials to enhance the binding ability of heterogeneous components and biomass materials and strengthen the interfacial interaction. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 This is a SEM image of the nickel and sulfur modified biomass derived carbon-based sulfide electrode material prepared in Example 1 of the present invention.
[0024] Figure 2 This is a TEM image of the nickel and sulfur modified biomass derived carbon-based sulfide electrode material prepared in Example 1 of the present invention.
[0025] Figure 3 This is the XRD pattern of the nickel and sulfur modified biomass derived carbon-based sulfide electrode material prepared in Example 1 of the present invention.
[0026] Figure 4 This is the LSV curve corresponding to the use of the nickel and sulfur modified biomass-derived carbon-based sulfide electrode material prepared in Example 1 of the present invention for urea-assisted water electrolysis to produce hydrogen.
[0027] Figure 5The nickel and sulfur modified biomass-derived carbon-based sulfide electrode material prepared in Example 1 of the present invention was used for the stability test corresponding to urea-assisted water electrolysis to produce hydrogen. DETAILED DESCRIPTION
[0028] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.
[0029] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0030] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0031] Example 1 A method for preparing a nickel-sulfur modified biomass-derived carbon-based sulfide electrode material comprises the following steps: (1) Pretreatment: Take 0.15 g of poplar wood fiber, immerse the obtained poplar wood fiber in deionized water, and treat it with ultrasound for 30 min to disperse the poplar wood fiber in the aqueous solution; (2) Preparation of precursor: 200.0 mg dopamine hydrochloride, 100.0 mg Tris base, 87.0 mg Co(NO3)2·6H2O, and 87.0 mg Ni(NO3)2·6H2O were added to the solution obtained in (1), and the mixed solution was stirred at room temperature for 24 h. After being fully mixed, it was washed by centrifugation with deionized water and dried in a vacuum drying oven at 60°C for 12 h. (3) Preparation of nickel- and sulfur-modified poplar fiber-derived carbon-based cobalt sulfide electrode material: The precursor obtained in step (2) was mixed with sulfur powder (mass ratio 1:1) and placed in a tube furnace. Under a nitrogen atmosphere, the mixture was heated at 5°C min -1 The temperature was raised to 500 °C at a rate of 5 °C min -1 The temperature was raised to 900°C at a heating rate of 1.5°C and kept at this temperature for 2 h, and finally cooled naturally to room temperature under nitrogen protection to obtain nickel- and sulfur-modified biomass-derived carbon-based sulfide electrode materials; The nickel-sulfur modified poplar fiber-derived carbon-based cobalt sulfide electrode material is based on poplar fiber-derived carbon as a matrix, on which sulfur-doped carbon nanotubes are uniformly loaded, and the tops of the carbon nanotubes are coated with nickel-modified cobalt sulfide nanoparticles.
[0032] The diameter of the carbon nanotubes is 20-80 nm, the length is 1-5 μm, and the chemical formula of the electrode material is (Co, Ni)9S8@SNC / SCWF.
[0033] An application of the nickel and sulfur-modified poplar fiber-derived carbon-based cobalt sulfide electrode material prepared in the above-mentioned embodiment in hydrogen production by electrolysis of water, specifically in urea-assisted hydrogen production by electrolysis of water, comprises the following steps: 5 mg of nickel and sulfur-modified poplar fiber-derived carbon-based cobalt sulfide electrode material is weighed, ground into powder, and placed in a centrifuge tube with 50 μL of deionized water, 200 μL of ethanol, and 10 μL of naphthol for ultrasonication for 30 minutes. Use a pipette to draw the mixed liquid droplets and apply them on the nickel foam, and place them in an oven to dry. Then, as a working electrode, it is placed in a 1.0 mol / L KOH + 0.5 mol / L CO(NH2)2 electrolyte for electrolysis reaction to obtain hydrogen.
[0034] in, Figure 1 This is a SEM image of the nickel-sulfur-modified poplar fiber-derived carbon-based cobalt sulfide electrode material prepared in Example 1 of the present invention. Figure 1 It can be seen that the carbon nanotube-coated nanoparticles are uniformly loaded on the surface of the poplar fiber-derived carbon, specifically, the sulfur-doped carbon nanotube-coated Ni-modified Co9S8 nanoparticles are anchored on the S-doped carbonized wood fibers.
[0035] Figure 2 XRD diagram of the carbon-based cobalt sulfide electrode material derived from nickel and sulfur-modified poplar fibers. Figure 2 It can be seen that strong diffraction peaks appear at diffraction angles of about 15.5°, 29.8°, 31.1°, 47.7°, and 52.1°, which correspond to the (111), (311), (222), (511), and (440) crystal planes of Co9S8, respectively (PDF#75-2023), proving that Co9S8 was successfully synthesized. Figure 2 No other diffraction peaks were observed, proving that nickel modified Co9S8 by replacing Co in the Co9S8 lattice.
[0036] The nickel-sulfur modified poplar fiber-derived carbon-based cobalt sulfide electrode material prepared in Example 1 of the present invention and the unmodified poplar fiber-derived carbon-based cobalt sulfide electrode material prepared in Comparative Example 1 were subjected to LSV test in 1.0 mol / L KOH + 0.5 mol / L CO(NH2)2 solution. The LSV comparison curves are shown in FIG. Figure 3 As shown. Figure 3 It can be seen that compared with the unmodified poplar fiber-derived carbon-based cobalt sulfide electrode material, the nickel-sulfur-modified poplar fiber-derived carbon-based sulfide electrode material prepared in the present invention exhibits better UOR catalytic activity, and only 1.38 V (vs. RHE) is required to obtain 50 mA / cm 2The urea oxidation current density is significantly lower than that of the unmodified poplar fiber-derived carbon-based sulfide electrocatalyst material (1.42 V). Subsequent replacement of the substrate material with reed also has good catalytic activity. Figure 4 To test the stability of the prepared nickel and sulfur modified poplar fiber derived carbon-based cobalt sulfide electrode material, the electrolyte was 1.0 mol / L KOH + 0.5 mol / L CO(NH2)2 at 50 mA / cm 2 The current density did not change significantly when the electrolysis was continued for 60 h under the current density condition, indicating that it has good stability.
[0037] Example 2 A method for preparing a nickel-sulfur modified biomass-derived carbon-based sulfide electrode material: (1) Pretreatment: Weigh 0.15 g of reed fiber, soak the obtained reed fiber in deionized water, and ultrasonically treat it for 30 min to make the reed fiber evenly dispersed in the aqueous solution; (2) Preparation of precursor: 200.0 mg dopamine hydrochloride, 100.0 mg Tris base, 87.0 mg Co(NO3)2·6H2O, and 87.0 mg Ni(NO3)2·6H2O were added to the solution obtained in (1), and the mixed solution was stirred at room temperature for 24 h. After being fully mixed, it was washed by centrifugation with deionized water and dried in a vacuum drying oven at 60°C for 12 h. (3) Nickel and sulfur modified reed fiber derived carbon-based cobalt sulfide electrode material: The precursor obtained in step (2) was placed in a tube furnace and heated at 5°C min under a nitrogen atmosphere. -1 The temperature was raised to 500 °C at a rate of 5 °C min -1 The temperature was raised to 900°C at a heating rate of , kept at this temperature for 2 h, and finally naturally cooled to room temperature under nitrogen protection to obtain nickel and sulfur-modified reed fiber-derived carbon-based cobalt sulfide electrode material.
[0038] The nickel-sulfur modified reed-derived carbon-based cobalt sulfide electrode material is based on reed-derived carbon as a matrix, on which sulfur-doped carbon nanotubes are uniformly loaded, and the tops of the carbon nanotubes are coated with nickel-modified cobalt sulfide particles.
[0039] The diameter of the carbon nanotubes is 20-80 nm, the length is 1-5 μm, and the chemical formula of the electrode material is (Co, Ni)9S8@SNC / SCWF.
[0040] The nickel and sulfur modified reed fiber derived carbon-based cobalt sulfide electrode material of Example 2 was applied in the same manner as in Example 1. The subsequent electrochemical performance data of the electrocatalytic material in Example 2 showed that 1.40 V (vs. RHE) was required to obtain 50 mA / cm 2 The current density of urea oxidation is
[0041] Comparative Example 1 A method for preparing a sulfur-modified poplar fiber-derived carbon-based cobalt sulfide electrode material: (1) Pretreatment: Take 0.15 g of poplar wood fiber, immerse the obtained poplar wood fiber in deionized water, and treat it with ultrasound for 30 min to disperse the poplar wood fiber in the aqueous solution; (2) Preparation of precursor: 200.0 mg dopamine hydrochloride, 100.0 mg Tris base, and 87.0 mg Co(NO3)2·6H2O were added to the solution obtained in (1), and the mixed solution was stirred at room temperature for 24 h. After being fully mixed, it was washed by centrifugation with deionized water and dried in a vacuum drying oven at 60°C for 12 h. (3) Preparation of unmodified poplar fiber-derived carbon-based cobalt sulfide electrode material: The precursor obtained in step (2) was mixed with sulfur powder (mass ratio 1:1) and placed in a tube furnace. Under a nitrogen atmosphere, the mixture was heated at 5°C / min. -1 The temperature was raised to 500 °C at a rate of 5 °C min -1 The temperature was raised to 900 °C at a heating rate of 1.5 °C and kept at this temperature for 2 h, and finally cooled naturally to room temperature under nitrogen protection to obtain an unmodified biomass-derived carbon-based sulfide electrode material; The same method as in Example 1 was used to apply the unmodified biomass-derived carbon-based sulfide electrode material of Comparative Example 1. The final experimental results showed that the subsequent electrochemical performance data of the electrocatalytic material in Comparative Example 1 required 1.42 V (vs. RHE) to obtain 50 mA / cm 2 The current density of urea oxidation is
Claims
1. A method for preparing a nickel-sulfur modified biomass-derived carbon-based sulfide electrode material, characterized in that: The following steps are involved: (1) Dispersing the biomass material evenly in deionized water; (2) adding dopamine hydrochloride, tris(hydroxymethyl)aminomethane, cobalt nitrate hexahydrate and nickel nitrate hexahydrate to the solution obtained in step (1), stirring the mixture at room temperature to react, and after the reaction is completed, washing and drying to obtain a precursor of a nickel-sulfur modified biomass-derived carbon-based sulfide electrode material; (3) The precursor obtained in step (2) is subjected to a high-temperature carbonization and sulfurization reaction with a sulfur source under a protective atmosphere, and upon completion of the reaction, a nickel-sulfur modified biomass-derived carbon-based sulfide electrode material is obtained.
2. The preparation method according to claim 1, characterized in that The biomass material in step (1) is poplar fiber or reed fiber, and the diameter of the poplar fiber or reed fiber is 10-14 um.
3. The preparation method according to claim 1, characterized in that: In step (1), the volume ratio of the biomass material added to the deionized water is 0.02-0.04:10, expressed in g / mL; the dispersion is performed by ultrasound, and the ultrasound time is controlled to be 0.5-1h.
4. The preparation method according to claim 1, characterized in that: In step (2), the concentration of dopamine hydrochloride is 0.020-0.022 mol / L, the concentration of tris(hydroxymethyl)aminomethane is 0.015-0.017 mol / L, the concentration of cobalt nitrate hexahydrate and nickel nitrate hexahydrate is 0.005-0.007 mol / L, and the reaction time is 22-26h.
5. The preparation method according to claim 1, characterized in that: The protective atmosphere in step (3) is nitrogen, and the mass ratio of the sulfur content in the sulfur-modified biomass-derived carbon-based electrode material precursor to the sulfur source is 0.8-1.2:0.8-1.2; the specific temperature of the high-temperature carbonization and sulfurization reaction is: firstly heating to 400-600°C at a heating rate of 2-10°C / min, and keeping warm for 1-4h; then heating to 890-910°C at a heating rate of 2-10°C / min, and keeping warm for 1-4h.
6. The preparation method according to claim 5, characterized in that: During the high-temperature carbonization and sulfurization reaction, the precursor and the sulfur source are respectively located at two ends of the reaction container and react synchronously.
7. A nickel-sulfur modified biomass-derived carbon-based sulfide electrode material, characterized in that: The electrode material is prepared by the preparation method according to any one of claims 1 to 6.
8. The electrode material according to claim 7, characterized in that The nickel-sulfur modified biomass derived carbon-based sulfide electrode material uses biomass carbon as a matrix, sulfur-doped carbon nanotubes are uniformly loaded on the matrix, and the tops of the sulfur-doped carbon nanotubes are coated with nickel-modified cobalt sulfide particles.
9. The electrode material according to claim 7, characterized in that The carbon nanotube has a diameter of 20-80 nm and a length of 1-5 μm. The chemical formula of the electrode material is (Co, Ni)9S8@SNC / SCWF.
10. An application of the nickel-sulfur modified biomass-derived carbon-based sulfide electrode material according to any one of claims 7 to 9, characterized in that: The nickel-sulfur modified biomass-derived carbon-based sulfide electrode material is used for urea-assisted water electrolysis to produce hydrogen.